2022
DOI: 10.3390/biomedicines11010039
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Menstrual-Blood-Derived Stem Cells in Endometriosis

Abstract: The human endometrium has a complex cellular composition that is capable of promoting cyclic regeneration, where endometrial stem cells play a critical role. Menstrual blood-derived stem cells (MenSC) were first discovered in 2007 and described as exhibiting mesenchymal stem cell properties, setting them in the spotlight for endometriosis research. The stem cell theory for endometriosis pathogenesis, supported by the consensual mechanism of retrograde menstruation, highlights the recognized importance that Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…From that time, the menstrual blood has attracted huge scientific interest, leading to a permanently increasing number of different research studies and possible applications of MenSCs in both experimental and clinical practices. In addition, the MenSCs, due to their origin, could have a higher level of stemness and better differentiation potential [ 49 ]. It has been shown that MenSCs, similar to other types of MSCs, possess MSCs-typical qualities such as high proliferative potential, self-renewal property and a multipotent differentiation into osteogenic, adipogenic and chondrogenic directions [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…From that time, the menstrual blood has attracted huge scientific interest, leading to a permanently increasing number of different research studies and possible applications of MenSCs in both experimental and clinical practices. In addition, the MenSCs, due to their origin, could have a higher level of stemness and better differentiation potential [ 49 ]. It has been shown that MenSCs, similar to other types of MSCs, possess MSCs-typical qualities such as high proliferative potential, self-renewal property and a multipotent differentiation into osteogenic, adipogenic and chondrogenic directions [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various hypotheses have been formulated for the development of endometriosis, such as implantation, metaplastic, and other hypotheses, but the retrograde menstruation theory still has the most supporters [ 162 , 163 ]. It assumes that fragments of the uterine mucosa may travel backwards through the fallopian tubes to the peritoneal cavity, where they may be implanted, and then grow and infiltrate adjacent structures.…”
Section: Egcg In the Treatment Of Benign Gynecological Diseasesmentioning
confidence: 99%
“…The most favored one describes how retrograde menstruation through the fallopian tubes could invade the peritoneal mesothelium, leading to diffuse implants of the disease and its blood supply for survival and growth [ 6 , 7 ]. The stem cell theory for endometriosis pathogenesis, supported by the consensual mechanism of retrograde menstruation, highlights the recognized importance that menstrual blood-derived stem cells have gained by potentially being directly related to the genesis, development, and maintenance of ectopic endometriotic lesions [ 8 ]. Endometriosis can be disabling and strongly compromise life quality along with the critical associated social-economic cost.…”
Section: Introductionmentioning
confidence: 99%